2023
DOI: 10.1002/fsn3.3563
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, sensory, and antioxidant characteristics of stirred‐type yogurt enriched with Lentinula edodes stipe powder

Abstract: The Lentinula edodes stipe (LES), a by‐product of L. edodes fruiting body processing, is rich in dietary fiber, protein, and polysaccharides, which can be served as the functional ingredient in dairy products. In this study, stirred yogurts fortified with 1%, 2%, and 3% LES were prepared, and the effects of LES on the changes in color, pH, titratable acidity (TA), viable lactic acid bacteria (LAB) cells, syneresis, viscosity, texture, and antioxidant activity of the flavored yogurt were monitored at the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Similarly, Tribst et al [32] found that yogurt made from sheep milk frozen at −18 °C for 1 month showed a faster pH drop over 28 d of storage than fresh milk, with no significant decrease in LAB counts (> 8.69 log CFU/mL). Studies have shown that yogurt experiences a simultaneous drop in pH and LAB counts over 21 days of storage [36,37]. ur results showed that the LAB counts in yogurt in the FM group decreased by 1 log CFU/mL after 21 days of storage; however, the decrease was greater in the other groups, especially in the −20 °C 180 d group (< 6 log CFU/mL).…”
Section: Analysis Of Post-acidification Degree Of Yak Yogurtmentioning
confidence: 83%
“…Similarly, Tribst et al [32] found that yogurt made from sheep milk frozen at −18 °C for 1 month showed a faster pH drop over 28 d of storage than fresh milk, with no significant decrease in LAB counts (> 8.69 log CFU/mL). Studies have shown that yogurt experiences a simultaneous drop in pH and LAB counts over 21 days of storage [36,37]. ur results showed that the LAB counts in yogurt in the FM group decreased by 1 log CFU/mL after 21 days of storage; however, the decrease was greater in the other groups, especially in the −20 °C 180 d group (< 6 log CFU/mL).…”
Section: Analysis Of Post-acidification Degree Of Yak Yogurtmentioning
confidence: 83%